신·재생에너지원별 온실가스 감축에 미치는 영향 분석 - 태양광과 풍력을 중심으로- - 이기배; 강주영 (신재생에너지, 2025)
In this study, the impact of solar and wind power generation on greenhouse gas (GHG) emissions was analyzed using panel data from 16 metropolitan local governments, excluding Sejong City, between 2010 and 2021. The analysis was conducted using a pooled mean group estimation model. The results indicated that a 1% increase in gross regional domestic product (GRDP) led to a 4.256% increase in GHG emissions; however, once GRDP surpassed a certain threshold, the trend reversed, with emissions decreasing by 0.585%. A 1% increase in energy consumption caused a 0.328% rise in GHG emissions. An increase of 1% in solar and wind power generation resulted in a 0.041% and 0.119% decrease in GHG emissions, respectively. This suggests that solar power generation would need to be increased by 24.39% to reduce GHG emissions by 1%, whereas wind power would need to be increased by 8.4%. In essence, increasing wind power demonstrates an approximate 2.9-fold greater effectiveness in reducing GHG emissions by 1% compared to increasing solar power.
Keywords: 온실가스 배출량; PMG 추정; 태양광 발전; 풍력 발전; Greenhouse gas emissions; Pooled mean group estimation; Solar power generation; Wind power generation